2022
DOI: 10.21162/pakjas/22.485
|View full text |Cite
|
Sign up to set email alerts
|

Phytobeneficial bacterial inoculants for common bean growth and productivity in nitrogen and phosphorus deficient soils

Abstract: Most of the soils are N and P-deficient and require high applications of chemical fertilizers to ensure optimal crop production. However, this practice poses in most cases serious environmental issues. In recent years, inoculation with beneficial bacteria has emerged as a safe and sustainable alternative to chemical fertilizers. In this context, we investigated the effect of two symbiotic Agrobacterium radiobacter strains (LMR670 and LMR676) and two plant growth-promoting rhizobacteria Bacillus sp. (M131) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…However, an excess of this can prevent nitrogen fixation. The authors of [42][43][44][45] evaluated the formation of nodules in Lupinus white proteoid roots with low P concentrations. They observed that at day 21 (Figure 7a-d), the number of nodules was greater in the treatment without P, but at 37 days, the nodules increased under the treatment with (+) P. In this research, the use of rizotrons was very useful when counting legume nodules between T2 and T3 (Table 3, Treatments in intercropping), and there are significant differences between treatments with the application of bacteria Burkholderia, which increased the nodulation.…”
Section: Nitrogen In Plant Tissue and The Maize Roots In Sandy Soilmentioning
confidence: 99%
“…However, an excess of this can prevent nitrogen fixation. The authors of [42][43][44][45] evaluated the formation of nodules in Lupinus white proteoid roots with low P concentrations. They observed that at day 21 (Figure 7a-d), the number of nodules was greater in the treatment without P, but at 37 days, the nodules increased under the treatment with (+) P. In this research, the use of rizotrons was very useful when counting legume nodules between T2 and T3 (Table 3, Treatments in intercropping), and there are significant differences between treatments with the application of bacteria Burkholderia, which increased the nodulation.…”
Section: Nitrogen In Plant Tissue and The Maize Roots In Sandy Soilmentioning
confidence: 99%